A fatal case of severe systemic varicella zoster infection in a patient with chronic use of immunosuppressive agents for cutaneous vasculitis. (2020) - Lin, Wei-Chen; Chang, Ching; Ko, Meng-Cheng; Lin, Shu-Min
Highlights: Varicella zoster virus infection can cause severe complication in immunocompromised patients. Early parenteral antiviral therapy is mandatory for preventing severe complication of varicella zoster virus infection. Post exposure prophylaxis varicella zoster immunoglobulin is beneficial for immunocompromised patients. Abstract: Acute varicella zoster virus (VZV) infection is a common condition in children, which is considered a mild, self-limited disease with diffuse skin vesicular rash. However, disseminated VZV infection with multiple organ involvement can occur in immunocompromised patients with impaired T cell immunity including solid or hematopoietic stem cell transplant recipients, receiving immunosuppressive therapy, leukemia, lymphoma, and HIV infection. Prompt antiviral therapy is mandatory in those immunocompromised persons. A 52 year-old man receiving chronic immunosuppressive drugs for his underlying leukocytoclastic vasculitis visited emergency department for diffuse skin vesicular rash that developed 4 days after contact with varicella zoster patients at his office. Despite prompt initiation of oral antiviral agents had been prescribed, rapid progression with septic shock, lactate acidosis, and disseminated intravascular coagulopathy occurred. The patient died within 24 h of intensive care unit admission. Varicella zoster infection commonly causes severe complications in adults receiving chronic immunosuppressive therapy. Post exposure prophylaxis varicella zoster immune globulin and early parenteral antiviral agents use after acute varicella virus infection may be mandatory in immunocompromised patients.